Aspirin as a Chemopreventive Agent for Cancer: a New Hope? - Miladiyah, Isnatin (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2015)
Introduction: inflammation has been shown to play a major role in the pathogenesis of cancer. Inflammatory process activates the immune system through pro-inflammatory mediators and subsequent triggers transformation into malignant cells. Some tumors or cancers has been associated with chronic infections, such as hepatitis B and C viruses (hepatocellular carcinoma), human papilloma virus (cervical cancer), Helicobacter pylori (gastric cancer and lymphoma), and prostatitis (prostate cancer). A considerable study have investigated the benefits of aspirin for the prevention and treatment of cancer or tumors. Objectives: This paper aims to describe the relationship between inflammation and cancer incidence, so that use of aspirin as an anti-inflammatory agent is a rational choice in the treatment and prevention of cancer. Conclusion: Aspirin potential for chemoprevention of various types of cancer. Considering the high risk of side effects of aspirin, aspirin is not intended as a routine therapy to prevent the occurrence of cancer.